Implementation of Collaborative Learning Methods in Improving Elementary School Students' Thinking Skills - Marsiah (AIQU: Journal Multidiscipliner of Science, 2024)
This research aims to analyze the effectiveness of collaborative learning methods in improving elementary school students' thinking skills. For collaborative learning to be effective, instructors must view teaching as a process of developing and enhancing students' learning abilities. The teacher's role is not to convey information, but to act as a learning facilitator. The research method used was quasi-experimental with a non-equivalent control group design. The sample consisted of 40 students in grades 5 and 6 who were divided into experimental groups and control groups. The experimental group took part in learning using a collaborative method, while the control group took part in conventional learning. The instruments used are thinking skills tests and questionnaires. The results showed that there was a significant increase in students' thinking skills in the experimental group compared to the control group. These findings imply that collaborative learning methods can be an effective strategy for developing students' thinking skills in the context of elementary school education.